- - Meszaros, Alexandra (Journal of Regional Security, 2024)
As a result of the transformation of the defence industry in the last three decades, it has become a pioneer in innovative technologies. This paper presents the revolution in the defence industry, focusing on the factors that have enabled this field to become one of the most innovative sectors. Data were collected through semi-structured, open-ended, in-depth interviews with twenty-five experts from ten European countries and analysed with qualitative content analysis. The results indicate the importance of defence alliances and collaborations, the role of small and medium-sized enterprises and start-ups, the significance of defence innovation in national strategy, and how the new circumstances may change the direction of innovation. However, despite the technological revolution in the defence industry and the aspiration to develop unmanned systems and technologies, humans will always remain a critical factor in strategic and tactical decision-making.